Global patterns of potential future plant diversity hidden in soil seed banks - Xuejun Yang (Nature Portfolio, 2021)
Soil seed banks are reservoirs of plant biodiversity. Here the authors compile a global dataset of soil seed banks in natural plant communities and report a spatially explicit analysis of environmental controls of seed bank density and diversity.